Techies Agronomics Corporation : Portative Cutter / Muhammad Ali Al Muntazar Mohd Suhaimi...[et al.] - Mohd Suhaimi, Muhammad Ali Al Muntazar; Wan Supian, Wan Muhammad Syakir Aiman; Abd Khalid, Muhammad Nazrul Afnan; Cik Alwi, Muhammad Nabil; Mohd Khalil, Amirulfikri; Rahman, Amin Farhan (2018)
Our company, Techies Agronomics Corporations will produce a product called Portative Cutter. This product will give high satisfaction to the customer who want to deal with agriculture and farming. Our product is not just use for farming only, but it can use also for home lawn cleaning process. It is because, our product can use as a grass cutter. So, with our product the customer can save their money from buy two products. It is because our product has two function in one system or body.